Preparation method for Electrode
Patent Information
- Application Number
- KR1020210013168
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-29
- Publication Date
- 2026-09-01
- Estimated Expiration
- 2041-01-29
Smart Images

Figure 112021012092461-PAT00007_ABST
Abstract
Description
Technology Field
[0001] The present application relates to a method for manufacturing an electrode. Background Technology
[0002] The application areas of energy storage technology are expanding to include mobile phones, camcorders, laptop PCs, and even electric vehicles.
[0003] One of the research fields of energy storage technology is rechargeable secondary batteries, and research and development are underway to improve the capacity density and specific energy of these secondary batteries.
[0004] The electrode (positive or negative electrode) applied to a secondary battery is typically manufactured by forming an active material layer containing an electrode active material and a binder on a current collector.
[0005] In order to smoothly induce electron movement between active materials and between the current collector and the active material layer at the electrodes of a secondary battery, adhesion between active material particles and adhesion between the active material layer and the current collector must be ensured.
[0006] Furthermore, if the adhesion between particles within the active material layer is insufficient, particles may detach from the electrodes, which degrades the stability and performance of the battery. For example, particles detached from the surfaces of the negative and positive electrodes due to insufficient adhesion can cause microshorts inside the battery, leading to performance degradation and potentially causing fires due to short circuits.
[0007] If the adhesion between the active material layer and the current collector decreases, the electron mobility between the active material layer and the current collector decreases, which can also cause a deterioration in speed characteristics and cycle characteristics.
[0008] The adhesion between particles in the active material layer, or the adhesion between the active material layer and the current collector, is secured by the binder.
[0009] Therefore, introducing more binder into the active material layer can secure higher adhesion.
[0010] However, in such cases, as the proportion of the active material decreases as the proportion of the binder increases, problems such as increased electrode resistance and decreased conductivity occur, leading to a decrease in the performance of the battery. The problem to be solved
[0011] The present application relates to a method for manufacturing an electrode. One objective of the present application is to provide a method for manufacturing an electrode comprising a current collector and an active material layer, wherein the method secures a high level of inter-particle adhesion relative to the binder content in the active material layer and adhesion between the active material layer and the current collector. means of solving the problem
[0012] Among the physical properties mentioned in this specification, those properties in which the measurement temperature affects the result are results measured at room temperature, unless otherwise specifically stated.
[0013] The term "room temperature" refers to a natural temperature that has not been heated or cooled, and means, for example, any temperature within the range of 10°C to 30°C, about 23°C, or about 25°C. In addition, the unit of temperature in this specification is Celsius (°C) unless otherwise specifically defined.
[0014] Among the physical properties mentioned in this specification, those whose results are affected by the measured pressure are results measured at atmospheric pressure, unless otherwise specifically stated.
[0015] The term atmospheric pressure refers to natural pressure that is not pressurized or depressurized, and typically means about 1 atmosphere of atmospheric pressure.
[0016] In this specification, for physical properties where the measured humidity affects the result, said physical property is a physical property measured at natural humidity that is not specifically controlled under the above-mentioned ambient temperature and / or atmospheric pressure conditions.
[0017] An electrode manufactured by the method of the present application comprises a current collector; and an active material layer present on one surface of the current collector. FIG. 1 is a cross-sectional view of such an electrode and shows a structure including a current collector (100) and an active material layer (200). In the electrode structure, the active material layer may be formed in contact with the surface of the current collector, or another layer may exist between the current collector and the active material layer. For example, as described below, an intermediate layer may exist between the current collector and the active material layer.
[0018] The above active material layer may include at least an electrode active material and a binder.
[0019] According to the manufacturing method of the present application, the distribution of the binder within the active material layer as described above, particularly the distribution of the binder within the active material layer adjacent to the current collector, can be controlled, and as a result of this control, high adhesion between particles within the active material layer can be secured, and at the same time, high adhesion between the active material layer and the current collector can be secured.
[0020] The active material layer contains an electrode active material and a binder, and adhesion is primarily exerted by the binder. Therefore, to ensure adhesion, it is necessary to place as much binder as possible at the locations where adhesion is required.
[0021] However, to achieve this, the affinity of each component in the slurry used for forming the active layer, or the affinity between each component in the slurry and the current collector, must be carefully considered. Furthermore, since the binder migrates to the upper part of the active layer during the electrode formation process or after electrode manufacturing, controlling the position of the binder is a difficult task, and such control is even more difficult when the binder content in the slurry is low. For example, as conceptually illustrated in FIG. 2, the binder (2001) typically present in the active material layer migrates to the upper part of the active material layer during and / or after electrode manufacturing, making it difficult to distribute the binder (2001) between the electrode active material (1001) and the current collector (100). In other words, among the binders distributed on the current collector, only a portion contributes to the improvement of adhesion, and this tendency becomes even greater when the proportion of binder in the active material layer is low.
[0022] According to the manufacturing method of the present application, an electrode capable of achieving excellent adhesion even with a low binder content can be provided by intensively distributing a binder in a part where adhesion improvement is required during the manufacturing process of the electrode (e.g., between the surface of the current collector and the electrode active material).
[0023] According to the manufacturing method of the present application, the ratio of the binder's occupied area, confirmed by a standard peel test, can be controlled to a high level relative to the binder content included in the active material layer.
[0024] The ratio of the occupied area of the term binder is the percentage (100 × A1 / A2) of the area (A1) where the binder component is confirmed to exist on the surface of the current collector after the standard peel test described below, relative to the total surface area (A2) of the current collector. The area where the binder component is confirmed to exist above can be confirmed in the manner described in the example through FE-SEM (Field Emission Scanning Electron Microscope) analysis. In the above confirmation process, the area where the binder component is confirmed to exist contains the binder, and in some cases, may also contain other additional components (e.g., thickeners, etc.).
[0025] In one example, the ratio (A / W) of the occupied area ratio of the binder and the content (W) of the electrode active material in the active material layer, as confirmed in the following standard peel test performed on an electrode manufactured by the manufacturing method of the present application, may be 17 or more.
[0026] Since the unit of the above occupied area ratio A is % and the unit of the binder content is weight % (wt%), the unit of the above ratio A / W is wt -1 It could be.
[0027] The content of the binder is substantially the same as the ratio of the binder content in the solid portion (the portion excluding the solvent) of the slurry when the composition of the slurry in the electrode manufacturing process is known. In addition, when the composition of the slurry in the electrode manufacturing process is unknown, the content of the binder can be confirmed through TGA (Thermogravimetric analysis) analysis of the active material. For example, when applying an SBR (Styrene-Butadiene Rubber) binder as a binder, the content of the binder can be confirmed by performing TGA analysis on the active material layer and determining the content of the SBR binder obtained from the decrease of 370°C to 440°C in the temperature-mass curve obtained by increasing the temperature at a rate of 10°C per minute.
[0028] The above ratio A / W is 17.5 or more, 18 or more, 18.5 or more, 19 or more, 19.5 or more, 20 or more, 20.5 or more, 21 or more, 21.5 or more, 22 or more, 22.5 or more, 23 or more, 23.5 or more, 24 or more, 24.5 or more, 25 or more, or 25.5 or more in other examples, or 50 or less, 49 or less, 48 or less, 47 or less, 46 or less, 45 or less, 44 or less, 43 or less, 42 or less, 41 or less, 40 or less, 39 or less, 38 or less, 37 or less, 36 or less, 35 or less, 34 or less, 33 or less, 32 or less, 31 or less, 30 or less, 29 or less, 28 or less, 27 or less, 26 or less, 25 or less, 24 It may be less than or equal to 23, less than or equal to 22, less than or equal to 21, less than or equal to 20, less than or equal to 19, or less than or equal to 18.
[0029] Under the above A / W ratio, it is possible to provide an electrode that ensures a high level of adhesion compared to the applied binder.
[0030] In the present application, the A / W ratio can be achieved by controlling the composition of the slurry (e.g., affinity of the solvent and binder), the affinity of each component in the slurry with the surface of the current collector, and / or the average particle size of the particulate matter in the slurry.
[0031] In this specification, the average particle size of the particulate material is the so-called D50 particle size or median diameter obtained by laser diffraction, and the method for obtaining this particle size is described in the examples. Furthermore, for example, in the case where the active material layer is a rolled layer, the average particle size mentioned in this specification for the particulate binder and particulate active material within the active material layer is the average particle size before rolling, unless specifically otherwise specified.
[0032] In one example, when two types of particulate binders (or electrode active materials) with different average particle sizes exist within the active material layer, the average particle size, taking into account the weight fractions of the two types of particulate binders, may be defined in this specification as the average particle size of the particulate binder (or electrode active material). For example, if a particulate binder (or electrode active material) with an average particle size D1 exists with a weight of W1 and a particulate binder (or electrode active material) with an average particle size D2 exists with a weight of W2, the average particle size D may be defined as D = (D1 × W1 + D2 × W2) / (W1 + W2). When verifying the above, the particle sizes D1 and D2 and the weights W1 and W2 are each values of the same unit.
[0033] The above standard peel test is performed using 3M’s Scotch Magic Tape Cat. 810R. To perform the standard peel test, the electrode is first cut to a size of approximately 20 mm in width and 100 mm in length. The Scotch Magic Tape Cat. 810R is also cut to a size of 10 mm in width and 60 mm in length. Then, as shown in FIG. 4, the Scotch Magic Tape Cat. 810R (300) is attached in a cross shape on the active material layer (200) of the electrode. The attachment can be performed so that the standard peel test is performed such that the Magic Tape Cat. 810R (300) protrudes to a certain extent. Then, the protruding part is grasped and the Magic Tape Cat. 810R (300) is peeled off. At this time, the peeling speed and peeling angle are not specifically limited, but the peeling speed can be set to approximately 20 mm / sec and the peeling angle to approximately 30 degrees. In addition, the above Scotch Magic Tape Cat. 810R (300) is attached by rolling the surface of the tape once back and forth with a roller having a weight of about 1 kg and a radius and width of 50 mm and 40 mm, respectively, after attaching the tape.
[0034] When the Scotch Magic Tape Cat. 810R (300) is peeled off through the above process, the components of the active material layer (200) are peeled off together with the Scotch Magic Tape Cat. 810R (300). Then, the above process is repeated using a new Scotch Magic Tape Cat. 810R (300).
[0035] This process can be performed until the components of the active material layer (200) are not visible on the Scotch Magic Tape Cat. 810R (300), thereby allowing the standard peel test to be conducted.
[0036] It can be determined that the active material layer (200) is not present on the Scotch Magic Tape Cat. 810R (300) by comparing the surface of the Scotch Magic Tape peeled from the active material layer with the surface of the unused Scotch Magic Tape, and if the brightness of both is substantially the same, it can be determined that the active material layer is not present (visual observation).
[0037] The specific method for conducting the standard peel test is described in the examples.
[0038] After the standard peel test as described above, the ratio of the binder's occupied area on the current collector can be verified.
[0039] The type of current collector applied in this application is not particularly limited, and known current collectors may be used. To realize the aforementioned ratio A / W, the surface characteristics (water contact angle, etc.) of the current collector may be controlled as described below. As for the current collector, for example, a film, sheet, or foil made of stainless steel, aluminum, nickel, titanium, calcined carbon, copper, carbon, nickel, titanium, or stainless steel surface-treated with silver, aluminum-cadmium alloy, etc. may be used. To realize the desired network region and blank region, one of the above current collectors having the surface characteristics described below may be selected, or the surface characteristics may be controlled by additional processing.
[0040] The thickness and shape of the entire house are not particularly restricted, and an appropriate type is selected within the known range.
[0041] The active material layer formed on the current collector includes an electrode active material and a binder.
[0042] Known materials may be used as binders, and components known to contribute to the bonding of components such as active materials within the active material layer and to the bonding of the active material layer and the current collector may be used. As binders that can be applied, one or a combination of two or more selected from PVDF (Poly(vinylidene fluoride)), PVA (poly(vinyl alcohol)), polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, SBR (Styrene-Butadiene rubber), fluororubber, and other known binders may be used.
[0043] To form a suitable network region, it is appropriate to use a particulate binder.
[0044] When a particulate material is used as an electrode active material, the ratio of the particle size between the particulate binder and the electrode active material layer can be controlled to control the distribution of the binder within the electrode active material layer.
[0045] For example, the ratio (D1 / D2) of the average particle size (D1, unit nm) of the particulate electrode active material and the average particle size (D2, unit nm) of the particulate binder may be within the range of 10 to 1,000. In other examples, the ratio (D1 / D2) may be 20 or more, 30 or more, 40 or more, 50 or more, 60 or more, 70 or more, 80 or more, 90 or more, 100 or more, 110 or more, 120 or more, or 130 or more, or 900 or less, 800 or less, 700 or less, 600 or less, 500 or less, 400 or less, 300 or less, 200 or less, or 150 or less.
[0046] In the above example, the binder may have an average particle size (D2) within the range of 50 nm to 500 nm. In another example, the average particle size (D2) of the binder may be about 70 nm or more, about 90 nm or more, about 110 nm or more, about 130 nm or more, or about 140 nm or more, or about 480 nm or less, about 460 nm or less, 440 nm or less, 420 nm or less, 400 nm or less, about 380 nm or less, about 360 nm or less, about 340 nm or less, about 320 nm or less, about 300 nm or less, about 280 nm or less, about 260 nm or less, about 240 nm or less, about 220 nm or less, about 200 nm or less, about 180 nm or less, or about 160 nm or less.
[0047] In the above example, the average particle size (D1) of the electrode active material may be within the range of 1 μm to 100 μm. In another example, the average particle size (D1) may be about 3 μm or more, about 5 μm or more, about 7 μm or more, about 9 μm or more, about 11 μm or more, about 13 μm or more, about 15 μm or more, about 17 μm or more, or about 19 μm or more, or about 90 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, 50 μm or less, 40 μm or less, 30 μm or less, or about 20 μm or less.
[0048] The above average particle sizes D1 and D2 are the average particle sizes of each material in the slurry applied for manufacturing the active material layer. Therefore, when the actual electrode is manufactured through a rolling process, there may be some difference from the average particle sizes D1 and D2 of each component identified in the active material layer.
[0049] Although the reason is not clear, it is expected that due to the particle size ratio above, a dispersion state of the binder is achieved in the slurry during the electrode manufacturing process, which allows the desired binder location to be achieved, and the binder migration phenomenon is also appropriately controlled.
[0050] In addition, for the formation of a suitable network region, it may be advantageous to use a binder having a solubility parameter within the range described below as the binder.
[0051] In the present application, a high level of adhesion can be secured while maintaining a relatively low proportion of binder within the active material layer. For example, the proportion of the binder within the active material layer may be approximately 0.5 to 10 weight percent. In other examples, the proportion may be further controlled within a range of approximately 1 weight percent or more, 1.5 weight percent or more, 2 weight percent or more, 2.5 weight percent or more, 3 weight percent or more, 3.5 weight percent or more, or 4 weight percent or more, and / or within a range of approximately 9.5 weight percent or less, 9 weight percent or less, 8.5 weight percent or less, 8 weight percent or less, 7.5 weight percent or less, 7 weight percent or less, 6.5 weight percent or less, 6 weight percent or less, 5.5 weight percent or less, 5 weight percent or less, or 4.5 weight percent or less.
[0052] The electrode active material included in the active material layer may be a positive electrode active material or a negative electrode active material, and the specific type is not particularly limited. For example, positive electrode active materials include LiCoO2, LiNiO2, LiMn2O4, LiCoPO4, LiFePO4, LiNiMnCoO2, and LiNi 1-x-yz Co x M1 y M2 z O2(M1 and M2 are independently selected from the group consisting of Al, Ni, Co, Fe, Mn, V, Cr, Ti, W, Ta, Mg, and Mo, and x, y, and z are independently atomic fractions of oxide composition elements as 0 Active materials including those satisfying x < 0.5, 0 ≤ y < 0.5, 0 ≤ z < 0.5, 0 < x+y+z ≤ 1) can be used, and as a negative electrode active material, active materials including natural graphite, artificial graphite, carbonaceous materials; lithium-containing titanium composite oxide (LTO), metals (Me) such as Si, Sn, Li, Zn, Mg, Cd, Ce, Ni, or Fe; alloys composed of said metals (Me); oxides of said metals (Me) (MeOx); and composites of said metals (Me) and carbon can be used.
[0053] In this application, it is possible to secure excellent adhesion while maintaining a relatively high proportion of the active material within the active material layer.
[0054] For example, the active material in the active material layer may be in the range of 1,000 to 10,000 parts by weight relative to 100 parts by weight of the binder. The above ratio may be 1500 parts by weight or more, 2000 parts by weight or more, 2500 parts by weight or more, 3000 parts by weight or more, 3500 parts by weight or more, 4000 parts by weight or more, or 4500 parts by weight or more, or 9500 parts by weight or less, 9000 parts by weight or less, 8500 parts by weight or less, 8000 parts by weight or less, 7500 parts by weight or less, 7000 parts by weight or less, 6500 parts by weight or less, 6000 parts by weight or less, 5500 parts by weight or less, 5000 parts by weight or less, 4500 parts by weight or less, 4000 parts by weight or less, 3500 parts by weight or less, 3000 parts by weight or less, or 2500 parts by weight or less.
[0055] The active material layer may additionally include other necessary components in addition to the above components. For example, the active material layer may additionally include a conductive material. As for the conductive material, known components may be used without special limitations as long as they exhibit conductivity without causing chemical changes in the current collector and the electrode active material. For example, as the conductive material, one or more types selected from graphite such as natural graphite or artificial graphite; carbon black such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, or nickel powder; zinc oxide; conductive whiskey such as potassium titanate; and conductive metal oxide group polyphenylene derivatives such as titanium oxide may be used.
[0056] The content of the conductive material is controlled as needed and is not specifically limited, but it may typically be included in an appropriate ratio within the range of 0.1 to 20 parts by weight or 0.3 to 12 parts by weight relative to 100 parts by weight of the active material. A method of determining the content of the conductive material to an appropriate level by considering the cycle life of the battery is known.
[0057] The active material layer may also include other known components required in addition to the above components (e.g., thickeners such as carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, or regenerated cellulose).
[0058] There are no specific limitations on the thickness of the active material layer, and it can be controlled to have an appropriate thickness considering the desired performance.
[0059] For example, the thickness of the active material layer may be within the range of about 10 to 500 μm. In other examples, the thickness may be about 30 μm or more, 50 μm or more, 70 μm or more, 90 μm or more, or 100 μm or more, or about 450 μm or less, 400 μm or less, 350 μm or less, 300 μm or less, 250 μm or less, 200 μm or less, or 150 μm or less.
[0060] The active material layer may be formed to have a certain level of porosity. The porosity is typically controlled by rolling during the manufacturing process of the electrode. The active material layer may have a porosity of approximately 35% or less. The porosity may be further controlled within the range of 33% or less, 31% or less, 29% or less, or 27% or less, and / or within the range of 5% or more, 7% or more, 9% or more, 11% or more, 13% or more, 15% or more, 17% or more, 19% or more, 21% or more, 23% or more, or 25% or more. The rolling process controlled to have the porosity may contribute to the formation of the network region and blank region intended in this application, as described below. In the above, the porosity is a value calculated by comparing the ratio of the difference between the actual density of the active material layer and the density after rolling, and a method of calculating the porosity of the active material layer in this manner is known.
[0061] In order to achieve a proper binder distribution during the manufacturing process of the electrode, an additional layer may be present to control the surface characteristics of the current collector.
[0062] For example, an intermediate layer containing a silane compound may exist between the active material layer and the current collector in the above electrode.
[0063] In this case, there are no special restrictions on the type of intermediate layer, as long as it is capable of achieving the surface characteristics of the entire house described later.
[0064] For example, the above intermediate layer may be a layer containing a silane compound of the following chemical formula 1.
[0065] [Chemical Formula 1]
[0066]
[0067] In Chemical Formula 1, R1 is an alkyl group having 6 or fewer carbon atoms or an alkenyl group having 6 or fewer carbon atoms, and the alkyl group of R1 may optionally be substituted with one or more amino groups, and R2 to R4 are each independently alkyl groups having 1 to 4 carbon atoms.
[0068] The alkyl group or alkenyl group in the above chemical formula 1 may be straight-chain, branched, or cyclic, and in suitable examples, may be a straight-chain alkyl group or alkenyl group.
[0069] In one example, R1 of Formula 1 may be a straight-chain alkyl group having 1 to 6 carbon atoms, 1 to 4 carbon atoms, or 2 to 4 carbon atoms, a straight-chain alkenyl group having 2 to 6 carbon atoms, 2 to 4 carbon atoms, or 2 to 4 carbon atoms, or a straight-chain aminoalkyl group having 1 to 6 carbon atoms, 1 to 4 carbon atoms, or 2 to 4 carbon atoms.
[0070] The intermediate layer may contain the above-mentioned silane compound as a main component, for example, the content of the above-mentioned silane compound in the intermediate layer may be 70 wt% or more, 75 wt% or more, 80 wt% or more, 85 wt% or more, 90 wt% or more, or 95 wt% or more. The upper limit of the content of the above-mentioned silane compound in the intermediate layer is 100 wt%. If a component other than the above-mentioned silane compound is present in the intermediate layer, that component may be a component such as a solvent used in the process of forming the intermediate layer, or an active material layer constituent component transferred from the active material layer.
[0071] The thickness of the intermediate layer can be appropriately set considering the desired surface characteristics, for example, within a range of approximately 0.5 to 50 μm.
[0072] The thickness mentioned above may be approximately 1 μm or more, 3 μm or more, 5 μm or more, 7 μm or more, or 9 μm or more in other examples, or approximately 45 μm or less, 40 μm or less, 35 μm or less, 30 μm or less, 25 μm or less, 20 μm or less, or 15 μm or less.
[0073] The electrode described above can be manufactured in the manner described below. Typically, the electrode is manufactured by coating a slurry onto a current collector, drying it, and then rolling it. In the present application, a desired distribution of binder can be achieved by controlling the composition of the slurry, the surface characteristics of the current collector coated with the slurry, and the drying and / or rolling conditions during the above process.
[0074] Accordingly, the manufacturing method of the present application may include at least the step of forming a layer of slurry on a current collector. At this time, the slurry may include at least a solvent, a binder, and an electrode active material.
[0075] In the manufacturing method of the present application above, a slurry in which a relatively hydrophobic binder is dispersed in a relatively polar solvent at a certain content may be applied.
[0076] In the manufacturing method of the present application, a layer is formed on a current collector using the above-described slurry. At this time, the method of forming the slurry layer is not particularly limited, and, for example, the layer can be formed using a known coating method. Although the reason is not clear, it is expected that when the above-described slurry is coated on a current collector, the dispersion state of the binder within the slurry, the affinity between the solvent of the slurry and the surface of the current collector, the affinity between the surface of the current collector and the binder of the slurry, and / or the relationship of particle sizes between them in the case of application of particulate matter, etc. are combined with each other to control the position of the binder in the desired form.
[0077] For example, the affinity between the solvent and the surface of the current collector affects the contact angle of the solvent on the surface of the current collector, and the contact angle can form a force in a certain direction within the slurry due to capillary action, etc., when the solvent evaporates. The affinity between the binder and the solvent and the amount of binder (and the particle size in the case of a particulate binder) affect the dispersion state of the binder within the slurry, and the affinity between the binder and the surface of the current collector affects the dispersion state of the binder within the slurry or the shape of the binder distribution on the surface of the current collector.
[0078] In this application, it was confirmed that the desired arrangement of the binder is achieved through the dispersion state of the binder and the evaporation mode of the solvent when a slurry of the composition described below is formed on a current collector of the surface characteristics described below, and the shear force within the slurry generated thereby.
[0079] For example, the slurry applied to the above manufacturing process may include a solvent. Typically, the solvent used is one that can adequately disperse slurry components such as electrode active materials, and examples include water, methanol, ethanol, isopropyl alcohol, acetone, dimethyl sulfoxide, formamide and / or dimethylformamide.
[0080] In the present application, it may be necessary to use a solvent having a dipole moment of approximately 1.3D or greater among the solvents described above. The dipole moment of the solvent may be further controlled in other examples to be within a range of about 1.35D or greater, 1.4D or greater, 1.45D or greater, 1.5D or greater, 1.55D or greater, 1.6D or greater, 1.65D or greater, 1.7D or greater, 1.75D or greater, 1.8D or greater, or 1.85D or greater, and / or within a range of about 5D or less, 4.5D or less, 4D or less, 3.5D or less, 3D or less, 2.5D or less, 2D or less, or 1.9D or less. The dipole moments of solvents are known for each solvent.
[0081] As a binder included in the above slurry, a suitable binder among the types described above may be selected and used. In order to achieve a desired dispersion state in the solvent, it may be necessary to use a binder having a solubility parameter of about 10 to 30 MPa1 / 2. In other examples, the solubility parameter may be 11 MPa1 / 2 or more, 12 MPa1 / 2 or more, 13 MPa1 / 2 or more, 14 MPa1 / 2 or more, 15 MPa1 / 2 or more, or 16 MPa1 / 2 or more, or 28 MPa1 / 2 or less, 26 MPa1 / 2 or less, 24 MPa1 / 2 or less, 22 MPa1 / 2 or less, 20 MPa1 / 2 or less, or 18 MPa1 / 2 or less. The solubility parameters of such binders can be verified through literature (e.g., Yanlong Luo et al., 2017, etc.). For example, among the types of binders mentioned above, a type having the solubility parameter mentioned above can be selected.
[0082] As the binder mentioned above, a particulate binder may be used. For example, it may be advantageous to use a binder in which the average particle size (D2) of the binder has a ratio (D1 / D2) with the average particle size (D1) of the electrode active material, which is also particulate, or a particulate binder having an average particle size within the aforementioned range, in order to achieve the desired dispersion state.
[0083] The content of the binder in the slurry can be controlled by considering the desired dispersion state. For example, the binder may be included in the slurry such that the concentration relative to the solvent (=100XB / (B+S), where B is the weight of the binder in the slurry (g) and S is the weight of the solvent in the slurry (g)) is approximately 0.1 to 10%. In other examples, the concentration may be 0.5% or more, 1% or more, 1.5% or more, 2% or more, 2.5% or more, 3% or more, or 3.5% or more, or 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less, or 2.5% or less.
[0084] The slurry may include the electrode active material in addition to the above components. As the electrode active material, an appropriate type may be selected from the types described above, and considering the contribution to the desired dispersion state, an electrode active material in the form of particles may be used that has an average particle size (D50 particle size) within the aforementioned range and has a ratio with the average particle size of the binder within the above range.
[0085] The ratio of the electrode active material in the slurry can be adjusted so that the ratio of the electrode active material in the active material layer can be achieved.
[0086] For example, the electrode active material in the above slurry may be included in a ratio within the range of 1,000 to 10,000 parts by weight relative to 100 parts by weight of the binder. The above ratio may be 1500 parts by weight or more, 2000 parts by weight or more, 2500 parts by weight or more, 3000 parts by weight or more, 3500 parts by weight or more, 4000 parts by weight or more, or 4500 parts by weight or more, or 9500 parts by weight or less, 9000 parts by weight or less, 8500 parts by weight or less, 8000 parts by weight or less, 7500 parts by weight or less, 7000 parts by weight or less, 6500 parts by weight or less, 6000 parts by weight or less, 5500 parts by weight or less, 5000 parts by weight or less, 4500 parts by weight or less, 4000 parts by weight or less, 3500 parts by weight or less, 3000 parts by weight or less, or 2500 parts by weight or less.
[0087] In addition to the above components, the slurry may also include other components, such as the conductive material and thickener described above, depending on the purpose.
[0088] The above slurry can be applied to the surface of the current collector. In this process, the application method is not particularly limited, and known application methods, such as spin coating, comma coating, and bar coating, can be applied.
[0089] The surface characteristics of the current collector to which the above slurry is applied can be controlled.
[0090] For example, the surface of the current collector to which the slurry is applied may have a water contact angle of 50 degrees or more. In other examples, the water contact angle may be further controlled within a range of approximately 100 degrees or less, 95 degrees or less, 90 degrees or less, 85 degrees or less, 80 degrees or less, or 75 degrees or less, and / or within a range of approximately 55 degrees or more, 60 degrees or more, 65 degrees or more, 70 degrees or more, 75 degrees or more, 85 degrees or more, or 90 degrees or more.
[0091] For example, the surface of the current collector to which the above slurry is applied may have a DM (diiodomethane) contact angle of 30 degrees or more. In other examples, the DM contact angle may be further controlled within a range of approximately 70 degrees or less, 65 degrees or less, 60 degrees or less, 55 degrees or less, 50 degrees or less, or 45 degrees or less, and / or within a range of approximately 35 degrees or more, 40 degrees or more, 45 degrees or more, 50 degrees or more, 55 degrees or more, or 60 degrees or more.
[0092] For example, the surface of the current collector to which the above slurry is applied may have a surface energy of 65 mN / m or less. In other examples, the surface energy may be 60 mN / m or less, 55 mN / m or less, 50 mN / m or less, 45 mN / m or less, 40 mN / m or less, 35 mN / m or less, or 30 mN / m or less, or 25 mN / m or more, 27 mN / m or more, or 29 mN / m or more.
[0093] For example, the surface of the current collector to which the above slurry is applied may have a dispersion energy of less than 45 mN / m. In other examples, the dispersion energy may be 40 mN / m or less, 35 mN / m or less, or 30 mN / m or less, or 23 mN / m or more, 25 mN / m or more, or 27 mN / m or more.
[0094] For example, the surface of the current collector to which the above slurry is applied may have a polar energy of 20 mN / m or less. The above-mentioned dispersed energy may be 18 mN / m or less, 16 mN / m or less, 14 mN / m or less, 12 mN / m or less, 10 mN / m or less, 8 mN / m or less, 6 mN / m or less, 4 mN / m or less, 2 mN / m or less, or 1.5 mN / m or less, or 0.5 mN / m or more, 1 mN / m or more, 1.5 mN / m or more, 2 mN / m or more, 2.5 mN / m or more, 3 mN / m or more, 3.5 mN / m or more, 4 mN / m or more, 4.5 mN / m or more, 5 mN / m or more, 5.5 mN / m or more, 6 mN / m or more, 6.5 mN / m or more, or 7 mN / m or more.
[0095] In the above, surface energy, dispersion energy, and polar energy are physical quantities that can be obtained using the OWRK (Owens-Wendt-Rabel-Kaelble) method based on water contact angle and DM contact angle.
[0096] A desired active material layer can be obtained by applying the aforementioned slurry to a current collector surface that satisfies at least one, two or more, or all of the surface characteristics mentioned above.
[0097] Among the current collectors described above, a current collector exhibiting the above water contact angle, etc. may be selected; however, since a typical current collector may not satisfy the above-described characteristics, surface treatment may be performed to satisfy the desired surface characteristics.
[0098] For example, the aforementioned intermediate layer may be formed on the surface of the current collector to satisfy the above surface characteristics. Accordingly, the intermediate layer may be formed on the surface of the current collector where the layer of the slurry is formed. In this case, the specific details regarding the intermediate layer are as described above.
[0099] The method of forming such an intermediate layer is not particularly limited, and, for example, it can be manufactured through coating, annealing, cleaning, and drying processes using a coating solution in which the silane compound is dispersed in a solvent.
[0100] However, the methods for controlling the surface characteristics of the current collector are not limited to the above, and the above surface characteristics can be satisfied by applying other known treatments, such as plasma treatment (especially hydrophobization treatment). Various treatment methods, such as plasma treatment, for controlling the surface characteristics of the current collector are also known.
[0101] After applying the slurry to the surface of the current collector with the above-mentioned surface characteristics, a drying process of the slurry may be performed. Although the conditions under which the drying process is performed are not particularly limited, it may be appropriate to control the drying temperature to a range of about 20°C to 400°C when considering the location of the desired binder, etc. The above drying temperature may be approximately 30°C or higher, 40°C or higher, 50°C or higher, 60°C or higher, 70°C or higher, 80°C or higher, 90°C or higher, 100°C or higher, 110°C or higher, 130°C or higher, 150°C or higher, 170°C or higher, 190°C or higher, 210°C or higher, or 225°C or higher, or 380°C or lower, 360°C or lower, 340°C or lower, 320°C or lower, 300°C or lower, 280°C or lower, 260°C or lower, 240°C or lower, 220°C or lower, 200°C or lower, 180°C or lower, 160°C or lower, 140°C or lower, 120°C or lower, 100°C or lower, or 95°C or lower.
[0102] The drying time can also be controlled by considering the dispersion state, such as the location of the desired binder, and, for example, can be adjusted within a range of about 10 seconds to 200 seconds. In other examples, the time may be further controlled within a range of 20 seconds or more, 30 seconds or more, 40 seconds or more, 50 seconds or more, 60 seconds or more, 70 seconds or more, 80 seconds or more, or 85 seconds or more, and / or within a range of 190 seconds or less, 180 seconds or less, 170 seconds or less, 160 seconds or less, 150 seconds or less, 140 seconds or less, 130 seconds or less, 120 seconds or less, 110 seconds or less, 100 seconds or less, or 95 seconds or less.
[0103] A rolling process may be performed following the drying process. In this case, the position of the binder, etc., may also be controlled by rolling conditions (e.g., pressure during rolling).
[0104] For example, the above rolling may be performed such that the porosity of the rolled slurry (active material layer) is about 35% or less. The desired arrangement of binder can be achieved by the pressure applied during rolling performed to have such porosity. In other examples, the porosity may be further adjusted within the range of 33% or less, 31% or less, 29% or less, or 27% or less, and / or within the range of 5% or more, 7% or more, 9% or more, 11% or more, 13% or more, 15% or more, 17% or more, 19% or more, 21% or more, 23% or more, or 25% or more.
[0105] The thickness of the above-mentioned rolled slurry (i.e., the active material layer) is approximately within the thickness range of the aforementioned active material layer.
[0106] During the manufacturing process of the electrode of the present application, in addition to the slurry coating, drying, and rolling, additional necessary processes (e.g., cutting process, etc.) may be performed.
[0107] The present application also relates to an electrochemical device comprising an electrode as described above, for example, a secondary battery.
[0108] The above electrochemical device may include the electrode as a positive electrode and / or a negative electrode. As long as the electrode of the present application is used as a negative electrode and / or a positive electrode, other configurations or manufacturing methods of the electrochemical device are not particularly limited, and known methods may be applied. Effects of the invention
[0109] The present application provides a method for manufacturing an electrode comprising a current collector and an active material layer, wherein the electrode can secure a high level of inter-particle adhesion relative to the binder content in the active material layer and adhesion between the active material layer and the current collector. Brief explanation of the drawing
[0110] FIG. 1 is a cross-sectional view of an exemplary electrode of the present application. Figure 2 is a conceptual diagram of the formation state of an active material layer in the prior art. Figure 3 is a conceptual diagram of the conditions under which a standard peel test is performed. Figures 4 to 9 are FE-SEM images of the current collector surfaces of Examples 1 to 6, respectively. FIGS. 10 to 12 are FE-SEM images of the current collector surfaces of Comparative Examples 1 to 3, respectively. Specific details for implementing the invention
[0111] The present application will be explained more specifically below through examples and comparative examples, but the scope of the present application is not limited to the following examples.
[0113] 1. Measurement of contact angle and surface energy
[0114] Contact angle and surface energy were measured using a KRUSS Drop Shape Analyzer (Manufacturer: KRUSS, Product Name: DSA100). 3 μL of water or DM (Diiodomethane) droplets were dropped at a rate of approximately 3 μl / sec, and their respective contact angles were measured using the Tangent Angle measurement method. Based on the contact angles of water and DM, the surface energy, dispersion energy, and polar energy were calculated using the Owens-Wendt-Rabel-Kaelble (OWRK) method.
[0116] 2. Standard peel test
[0117] A standard peel test was performed using 3M’s Scotch Magic Tape Cat. 810R. Samples were obtained by cutting the electrodes prepared in the examples or comparative examples to a size of approximately 20 mm in width and 100 mm in length. The Scotch Magic Tape Cat. 810R was attached to the active material layer of the obtained sample by reciprocating once using a roller weighing 1 kg, with a radius of 50 mm and a width of 40 mm. At this time, the Scotch Magic Tape was cut to a size of approximately 10 mm in width and 60 mm in length. As shown in Fig. 3, the Scotch Magic Tape and the electrode active material layer were attached in a cross pattern over a length of approximately 20 mm, and the protruding portion was grasped and peeled. The peeling speed and angle were set to a speed of approximately 20 mm / sec and an angle of approximately 30 degrees, respectively. A new Scotch Magic Tape was used for each peel. The above process was repeated until no active material layer components were transferred to the surface of the Scotch Magic Tape. Whether active material layer components were transferred was determined by visual inspection; if the contrast did not substantially change compared to the unused tape, it was determined that no active material layer components were transferred.
[0119] 3. Check the binder's occupied area
[0120] After the standard peel test, the area occupied by the binder on the surface of the current collector was determined. After the standard peel test, images were obtained by photographing the surface of the current collector at a magnification of 500x using an FE-SEM (Field Emission Scanning Electron Microscope) instrument (Manufacturer: HITACHI, Product Name: S4800). Using the Trainable Weka Segmentation Plug-in of Image J software (Manufacturer: Image J), the area where the surface of the current collector is not observed due to the presence of the binder and the area where the surface of the current collector is observed were distinguished, and the area occupied by the binder was measured based on this. In the above process, based on brightness, the area satisfying the criteria of a brightness of 80 or less and a brightness of 160 or more due to height within the closed curve formed by that area was designated as the area occupied by the binder, and the area that did not meet these criteria was designated as the area where the binder is not present.
[0122] 4. Confirmation of the average particle size (D50 particle size) of the particulate binder and electrode active material
[0123] The average particle size (D50 particle size) of the particulate binder and electrode active material was measured using a Marvern MASTERSIZER3000 instrument in accordance with ISO-13320 standards. Ethanol was used as the solvent for the measurement. When a laser is irradiated onto the particulate binder, etc. dispersed in the solvent, the laser is scattered by the binder, etc. dispersed in the solvent. Since the intensity and directionality values of the scattered laser vary depending on the particle size, the average diameter can be calculated by analyzing this using Mie theory. Through the above analysis, a volume-based cumulative graph of the particle size distribution was obtained by converting the diameter of the dispersed binder, etc. into the diameter of a sphere with the same volume, and the particle diameter (median diameter) at the cumulative 50% of the graph was designated as the average particle size (D50 particle size).
[0125] 4. Measurement of Adhesion
[0126] After rolling, the electrode was cut to a width of approximately 20 mm, and the adhesion strength was measured according to a known method for measuring the adhesion strength of an active material layer. During the adhesion strength measurement, the peel angle was set to 90 degrees, and the peel speed was set to approximately 5 mm / sec. After measurement, the average of the peaks that stabilized was defined as the adhesion strength.
[0128] Example 1.
[0129] Copper foil was used as the current collector, and after controlling the surface characteristics in the following manner, it was applied to the manufacture of the electrode.
[0130] First, a coating solution in which ethyl trimethoxysilane was dispersed in ethanol, a solvent, at a concentration of about 1 wt% was coated onto the surface of the copper foil using a bar coater to a thickness of about 10 μm. After coating, the surface was annealed at 100°C for about 5 minutes, washed with ethanol, and then dried again at 100°C for about 5 minutes to form a silane coating layer. The surface energy of the silane coating layer was about 29.7 mN / m, the dispersion energy was about 28.3 mN / m, and the polar energy was about 1.4 mN / m. In addition, the water contact angle was about 95 degrees, and the DM contact angle was about 60.4 degrees.
[0131] The slurry was prepared by mixing water, SBR (Styrene-Butadiene rubber) binder, a thickener (CMC, carboxymethyl cellulose), an electrode active material (1) (synthetic graphite (GT), average particle size (D50 particle size): 20 μm), and an electrode active material (2) (natural graphite (PAS), average particle size (D50 particle size): 15 μm) in a weight ratio of 51:2:0.6:37.1:9.3 (water:SBR:CMC:active material (1):active material (2)). In the above, water is a solvent with a dipole moment of about 1.84 D, and the SBR binder is a binder with a solubility parameter of about 16.9 MPa 1 / 2. The solubility parameter of the SBR binder is the value described in Yanlong Luo et al., 2017. In addition, the above SBR binder is a particulate binder, and the average particle size (D50 particle size, median particle size) was about 150 nm.
[0132] The above slurry was applied to the surface of the silane coating layer by a gap coating method to a thickness of about 280 μm and dried at a temperature of about 230°C for about 90 seconds. After drying, a slurry layer with a thickness of about 180 μm was obtained, and the dried slurry layer was rolled using a conventional electrode rolling mill to form an active material layer with a final thickness of about 110 μm and a porosity of about 26%.
[0133] The porosity of the above active material layer is a value calculated by comparing the ratio of the difference between the actual density and the density after rolling. In addition, considering the composition of the slurry, the content of the SBR binder in the active material layer of the electrode is about 4 wt%, and the content of the electrode active material (GT+PAS) is about 95 wt%.
[0135] Example 2.
[0136] Copper foil was used as the current collector, and after controlling the surface characteristics in the following manner, it was applied to the manufacture of the electrode.
[0137] A coating solution in which allyl trimethoxysilane was dispersed in ethanol, a solvent, at a concentration of about 1 wt% was coated onto the surface of the copper foil using a bar coater to a thickness of about 10 μm. After coating, the surface was annealed at 100°C for about 5 minutes, washed with ethanol, and then dried again at 100°C for about 5 minutes to form a silane coating layer. The surface energy of the silane coating layer was about 30.6 mN / m, the dispersion energy was about 29.5 mN / m, and the polar energy was about 1.1 mN / m. In addition, the water contact angle was about 95.8 degrees, and the DM contact angle was about 58.4 degrees.
[0138] Next, the same slurry used in Example 1 was applied to the surface of the silane coating layer by a gap coating method to a thickness of about 280 μm, and dried at a temperature of about 230°C for about 90 seconds. After drying, a slurry layer with a thickness of about 180 μm was obtained, and the dried slurry layer was rolled using a conventional electrode rolling mill to form an active material layer with a final thickness of about 110 μm and a porosity of about 26%.
[0139] The method of calculating the porosity of the above active material layer and the content of the SBR binder and electrode active material within the active material layer of the electrode are the same as in Example 1.
[0141] Example 3.
[0142] Copper foil was used as the current collector, and after controlling the surface characteristics in the following manner, it was applied to the manufacture of the electrode.
[0143] A coating solution in which 3-aminopropyl trimethoxysilane was dispersed in ethanol, a solvent, at a concentration of about 1 wt% was coated onto the surface of the copper foil using a bar coater to a thickness of about 10 μm. After coating, the surface was annealed at 100°C for about 5 minutes, washed with ethanol, and then dried again at 100°C for about 5 minutes to form a silane coating layer. The surface energy of the silane coating layer was about 28.3 mN / m, the dispersion energy was about 27.1 mN / m, and the polar energy was about 1.2 mN / m. In addition, the water contact angle was about 96.8 degrees, and the DM contact angle was about 62.6 degrees.
[0144] Next, the same slurry used in Example 1 was applied to the surface of the silane coating layer by a gap coating method to a thickness of about 280 μm, and dried at a temperature of about 230°C for about 90 seconds. After drying, a slurry layer with a thickness of about 180 μm was obtained, and the dried slurry layer was rolled using a conventional electrode rolling mill to form an active material layer with a final thickness of about 110 μm and a porosity of about 26%.
[0145] The method of calculating the porosity of the above active material layer and the content of the SBR binder and electrode active material within the active material layer of the electrode are the same as in Example 1.
[0147] Example 4.
[0148] A copper foil (Cu foil) with surface characteristics controlled in the same manner as in Example 1 was used as a current collector.
[0149] The slurry was prepared by mixing water, SBR (Styrene-Butadiene rubber) binder, a thickener (CMC, carboxymethyl cellulose), an electrode active material (1) (synthetic graphite (GT), average particle size (D50 particle size): 20 μm) and an electrode active material (2) (natural graphite (PAS), average particle size (D50 particle size): 15 μm) in a weight ratio of 48.5:1:0.5:45:5 (water:SBR:CMC:active material (1):active material (2)). In the above, water is a solvent with a dipole moment of about 1.84 D, and the SBR binder is a binder with a solubility parameter of about 16.9 MPa 1 / 2. The solubility parameter of the SBR binder is the value described in Yanlong Luo et al., 2017. In addition, the above SBR binder is a particulate binder, and the average particle size (D50 particle size, median particle size) was about 150 nm.
[0150] The above slurry was applied to the surface of the silane coating layer by a gap coating method to a thickness of about 280 μm and dried at a temperature of about 230°C for about 90 seconds. After drying, a slurry layer with a thickness of about 180 μm was obtained, and the dried slurry layer was rolled using a conventional electrode rolling mill to form an active material layer with a final thickness of about 110 μm and a porosity of about 26%.
[0151] The method for calculating the porosity of the active material layer is the same as in Example 1. In addition, considering the composition of the slurry, the content of the SBR binder in the active material layer of the electrode is about 2 wt%, and the content of the electrode active material is about 97 wt%.
[0153] Example 5.
[0154] A copper foil (Cu foil) with surface properties controlled in the same manner as in Example 2 was used as a current collector.
[0155] Next, the same slurry used in Example 4 was applied to the surface of the silane coating layer by a gap coating method to a thickness of about 280 μm, and dried at a temperature of about 230°C for about 90 seconds. After drying, a slurry layer with a thickness of about 180 μm was obtained, and the dried slurry layer was rolled using a conventional electrode rolling mill to form an active material layer with a final thickness of about 110 μm and a porosity of about 26%.
[0156] The method of calculating the porosity of the above active material layer and the content of the SBR binder and electrode active material within the active material layer of the electrode are the same as in Example 4.
[0158] Example 6.
[0159] A copper foil (Cu foil) with surface properties controlled in the same manner as in Example 3 was used as a current collector.
[0160] Next, the same slurry used in Example 4 was applied to the surface of the silane coating layer by a gap coating method to a thickness of about 280 μm, and dried at a temperature of about 230°C for about 90 seconds. After drying, a slurry layer with a thickness of about 180 μm was obtained, and the dried slurry layer was rolled using a conventional electrode rolling mill to form an active material layer with a final thickness of about 110 μm and a porosity of about 26%.
[0161] The method of calculating the porosity of the above active material layer and the content of the SBR binder and electrode active material within the active material layer of the electrode are the same as in Example 4.
[0163] Comparative Example 1.
[0164] The copper foil (Cu foil) used as the current collector was applied directly to the manufacture of the electrode without any separate treatment. The surface energy of the untreated copper foil surface was approximately 71.2 mN / m, the dispersion energy was approximately 45 mN / m, and the polar energy was approximately 26.2 mN / m.
[0165] Next, the same slurry used in Example 1 was applied to the surface of the copper foil layer by a gap coating method to a thickness of about 280 μm, and dried at a temperature of about 230°C for about 90 seconds. After drying, a slurry layer with a thickness of about 180 μm was obtained, and the dried slurry layer was rolled using a conventional electrode rolling mill to form an active material layer with a final thickness of about 110 μm and a porosity of about 26%.
[0166] The method of calculating the porosity of the above active material layer and the content of the SBR binder and electrode active material within the active material layer of the electrode are the same as in Example 1.
[0168] Comparative Example 2.
[0169] Copper foil was used as the current collector, and after controlling the surface characteristics in the following manner, it was applied to the manufacture of the electrode.
[0170] A coating solution in which dodecyl trimethoxysilane was dispersed in ethanol, a solvent, at a concentration of about 1 wt% was coated onto the surface of the copper foil using a bar coater to a thickness of about 10 μm. After coating, the surface was annealed at 100°C for about 5 minutes, washed with ethanol, and then dried again at 100°C for about 5 minutes to form a silane coating layer. The surface energy of the silane coating layer was about 27.7 mN / m, the dispersion energy was about 27.4 mN / m, and the polar energy was about 0.3 mN / m. In addition, the water contact angle was about 102.6 degrees, and the DM contact angle was about 62.2 degrees.
[0171] The same slurry used in Example 1 was applied to the surface of the silane coating layer by a gap coating method to a thickness of about 280 μm, and dried at a temperature of about 230°C for about 90 seconds. After drying, a slurry layer with a thickness of about 180 μm was obtained, and the dried slurry layer was rolled using a conventional electrode rolling mill to form an active material layer with a final thickness of about 110 μm and a porosity of about 26%.
[0172] The method of calculating the porosity of the above active material layer and the content of the SBR binder and electrode active material within the active material layer of the electrode are the same as in Example 1.
[0174] Comparative Example 3.
[0175] The copper foil (Cu foil) used as the current collector was applied directly to the manufacture of the electrode without any separate treatment. The surface energy of the untreated copper foil surface was approximately 71.2 mN / m, the dispersion energy was approximately 45 mN / m, and the polar energy was approximately 26.2 mN / m.
[0176] Next, the same slurry used in Example 4 was applied to the surface of the copper foil layer by a gap coating method to a thickness of about 280 μm, and dried at a temperature of about 230°C for about 90 seconds. After drying, a slurry layer with a thickness of about 180 μm was obtained, and the dried slurry layer was rolled using a conventional electrode rolling mill to form an active material layer with a final thickness of about 110 μm and a porosity of about 26%.
[0177] The method of calculating the porosity of the above active material layer and the content of the SBR binder and electrode active material within the active material layer of the electrode are the same as in Example 4.
[0179] Test Example 1. Calculation of Binder Occupancy Area
[0180] A standard peel test was performed on the electrodes of the examples and comparative examples in the manner described above, and the occupied area of the binder was confirmed. FIGS. 4 to 9 are FE-SEM images of Examples 1 to 6, respectively, and FIGS. 10 to 12 are FE-SEM images of Comparative Examples 1 to 3, respectively.
[0181] The results are listed in Table 1 below.
[0182] Examples Comparative example 1 2 3 4 5 6 1 2 3 Binder Occupancy Area Ratio (A) (%) 85.9 89.3 93.6 52.6 59 59.7 55.3 53.7 34.5 Binder content (W) (weight%) in the active material layer 4.1 4.1 4.1 2.3 2.3 2.3 4.1 4.1 2.3 A / W 21 21.8 22.8 22.9 25.7 26 13.5 13.1 15
[0183] From Table 1, it can be confirmed that in the case of the example, a high ratio of the binder's occupied area relative to the binder content in the active material layer is secured.
[0185] Test Example 2. Verification of Adhesion
[0186] The results of the adhesion strength evaluation for the examples and comparative examples are as shown in Table 2 below.
[0187] Examples Comparative example 1 2 3 4 5 6 1 2 3 Adhesion (gf / 20mm) 44 41.4 40.8 15.3 21.8 17.3 38.1 39.5 14.9
[0188] From Table 2, it can be confirmed that in the case of the example, high adhesive strength is secured relative to the binder content in the active material layer. Explanation of the symbols
[0189] 100: Whole house 200: Active material layer 300: Scotch Magic Tape 1001: Electrode active material 2001: Binder
Claims
Claim 1 The method comprises the step of forming a layer of slurry on a current collector, wherein the slurry comprises a solvent having a dipole moment of 1.3D or more and 2D or less; and a solubility parameter of 10 to 20 MPa 1 / 2 A method for manufacturing an electrode comprising a binder and an electrode active material within the range, wherein the water contact angle of the surface of a current collector on which the slurry layer is formed is 85 degrees or more and 100 degrees or less, the slurry comprises 1,000 to 10,000 parts by weight of an electrode active material per 100 parts by weight of binder, the surface energy of the surface of the current collector on which the slurry layer is formed is 65 mN / m or less, the dispersion energy of the surface of the current collector on which the slurry layer is formed is 40 mN / m or less, and the polarity energy of the surface of the current collector on which the slurry layer is formed is 20 mN / m or less. Claim 2 A method for manufacturing an electrode in which the binder is a particulate binder, wherein, in claim 1. Claim 3 A method for manufacturing an electrode according to claim 1, wherein the electrode active material and the binder are in the form of particles, and the ratio (D1 / D2) of the average particle size (D1) of the electrode active material and the average particle size (D2) of the binder is within the range of 10 to 1000. Claim 4 A method for manufacturing an electrode according to claim 1, wherein the binder is a particulate binder having an average particle size within the range of 50 nm to 500 nm. Claim 5 A method for manufacturing an electrode according to claim 1, wherein the slurry comprises a binder such that its concentration relative to the solvent is in the range of 0.1 to 10%. Claim 6 delete Claim 7 A method for manufacturing an electrode according to claim 1, wherein the DM (diiodomethane) contact angle of the surface of a current collector on which a layer of slurry is formed is 30 degrees or more. Claim 8 delete Claim 9 delete Claim 10 delete Claim 11 Method for manufacturing an electrode according to claim 1, wherein an intermediate layer comprising the following chemical formula 1 is present on the surface of a current collector on which a layer of slurry is formed: [Chemical Formula 1] In Chemical Formula 1, R1 is an alkyl group having 6 or fewer carbon atoms or an alkenyl group having 6 or fewer carbon atoms, and the alkyl group of R1 may optionally be substituted with one or more amino groups, and R2 to R4 are each independently alkyl groups having 1 to 4 carbon atoms. Claim 12 A method for manufacturing an electrode according to claim 1, further comprising a process of drying a layer of slurry formed on the surface of a current collector at a temperature within the range of 20°C to 400°C. Claim 13 A method for manufacturing an electrode according to claim 1, further comprising the step of rolling a slurry. Claim 14 A method for manufacturing an electrode according to claim 1, further comprising the step of rolling a slurry to achieve a porosity of 35% or less. Claim 15 A method for manufacturing an electrode according to claim 1, comprising: a current collector; and an active material layer existing on one surface of the current collector and comprising an electrode active material and a binder, wherein the ratio (A / W) of the binder content (W) in the active material layer to the ratio of the binder's occupied area on the surface of the current collector as confirmed in the following standard peel test is 17 or higher: Standard peel test: Scotch Magic Tape Cat. on the active material layer The above Scotch Magic Tape Cat. involves attaching and then removing the 810R. Repeat until the components of the active material layer are not identified on the 810R.
Citation Information
Patent Citations
Negative electrode for lithium-ion secondary battery
KR1020120066669A
Manufacturing method for battery electrodes
JP5522487B2
Electrode for lithium secondary battery and lithium secondary battery comprising the same
KR1020130084457A
Negative-pole material manufacturing method for lithium ion secondary battery and negative-pole material for lithium ion secondary battery
KR1020140051278A
A method for manufacturing an electrode for an electrochemical device
KR1020180036249A